The SMEs during Economic Slowdown in Poland. The Experiences from the Latest Global Financial Crisis. - Anna Bąkiewicz (International Journal of Small and Medium Enterprises and Business Sustainability, 2015)
The paper explores the reaction of small and medium enterprises in Poland to the latest economic slowdown. In order to show some regularities that occurred in the way the small businesses responded to the crisis numerous studies that represented different perspectives and methodologies are summarized in the paper. The experiences of Poland provide some convincing evidence that the resistance to the negative external factors of particular subsectors of the SMEs depends on the specific futures of small businesses. Moreover, it becomes evident that conservative business strategies adapted by the majority of the SMEs make the later more resistant to the crisis. Generally, the results of the study stand in opposition to the popular view in which small businesses are identified with dynamic entrepreneurship and development.